Analisis Kegagalan Front Drive Shaft Kanan Mobil - Yuriski Nasution; Yuriski Fair Nasution Chairika Nasution; DN Adnyana (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2021)
This paper discusses the failure that occurred on the right front drive shaft of a vehicle with the specification of S45C medium carbon steel material. The right front drive shaft receives several dynamic loads and torque so it must be strong to endure stress [1]. The right front drive shaft shows that there is an initial crack which causes the brittle fracture overload and is caused by sudden external loads. The purpose of this study is to determine the factors causing the failure and to provide a solution if a similar case occurs in components with the same material. Keywords: Front drive shaft right car, carbon steel medium S45C, brittle fracture over load, sudden impact load.